2016
DOI: 10.1186/s13013-016-0091-x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of 158 adult scoliosis treated by a bivalve polyethylene overlapping brace and reviewed at least 5 years after brace fitting

Abstract: BackgroundThe conservative orthopaedic treatment of adult scoliosis is very disappointing. In a series of 144 patients; only 25 % (33 cases) were monitored at 2 years of treatment. (Papadopoulos 2013). Thereby the literature typically focuses on a small number of patients, which limits the usefulness and relevance of its results. The brace effect on pain has been systematically described, but there is no publication on the effect of treatment on the Cobb angle and main clinical parameters.MethodsFrom a prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 4 publications
0
22
0
Order By: Relevance
“…An analysis of the proceedings from the SOSORT scientific meetings highlighted seven abstracts/oral presentations discussing the effects of bracing in adult populations. Four of these abstracts could be linked to studies that had been written up and already included in the review [20,21]. The remaining three abstracts focused on the effects of the SpineCor brace in adults [22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…An analysis of the proceedings from the SOSORT scientific meetings highlighted seven abstracts/oral presentations discussing the effects of bracing in adult populations. Four of these abstracts could be linked to studies that had been written up and already included in the review [20,21]. The remaining three abstracts focused on the effects of the SpineCor brace in adults [22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…It stabilizes the spine, improves the sagittal imbalance, and reduces the load in the lumbar spine. de Mauroy et al [77] have shown that a spinal brace is able to stabilize progressive curves in 80% of the adults with scoliosis [76].…”
Section: Treatmentmentioning
confidence: 99%
“…Spinal bracing has been advocated in the management of adult scoliosis, to halt progression of curves, restore sagittal balance, and treat pain and disability. The effectiveness of braces, however, has been controversial [77,80]. A number of studies opined that spinal braces do not halt curve progression.…”
Section: Spinal Bracingmentioning
confidence: 99%
See 2 more Smart Citations